Variation in total lipid content and fatty acid composition in the muscle of Bombayduck Harpodon nehereus (Hamilton, 1922) with respect to size and season - Rathod, Ramesh; Pal, Asim K; Chakraborty, Sushanta K; Gudipati, Venkateshwarlu (Indian Journal of Fisheries, 2013)
In view of the increased importance of fish lipids owing to their human health beneficial effects, the total lipid content and fatty acid composition in the muscle of Bombayduck (Harpodon nehereus) of different sizes harvested in different seasons were studied. Among the three seasons studied, total muscle lipids were significantly (p